An Empirical Study on the Influence of Agricultural Public Infrastructure on Total Factor Productivity of China’s Grain Production - Yang Yu and Pan Yuping (Contemporary Social Sciences, 2022)
A critical method of ensuring grain production is to increase the total factor productivity (TFP), and the key measure to increase the TFP of grain production lies in the construction of agricultural public infrastructure. For this topic, existing literature lacks systematic and empirical analysis. Therefore, research on the influence of agricultural public infrastructure on the TFP of China’s grain production has relatively strong policy implications and theoretical value. For this study, we collected panel data for grain inputs and outputs as well as for agricultural public infrastructure in China’s provinces (autonomous regions/municipalities) from 1990 to 2017, and adopted the stochastic frontier function (SFF) approach to measure the TFP of provincial-level grain production. Through this empirical study, we analyzed the influence of agricultural public infrastructures, such as irrigation, roads, and electric power facilities on the TFP of China’s agriculture. We found that such facilities have a positive influence on the TFP of grain production. Specifically, when the input for irrigation facilities is increased by 1 percent, the TFP of grain production will rise by 5.74 percent. Based on this finding, policy recommendations are proposed for enhancing grain TFP through agricultural public infrastructure construction.